The Morphology, Mitogenome, Phylogenetic Position, and Symbiotic Bacteria of a New Species of Sclerolinum (Annelida: Siboglinidae) in the South China Sea - Xu, Ting; Sun, Yanan; Wang, Zhi; Sen, Arunima; Qian, Pei-Yuan; Qiu, Jian-Wen (Frontiers in Marine Science, 2022)
Sclerolinum annulatus n. sp. (Annelida: Siboglinidae) is described based on specimens collected from soft sediment of the Haima cold seep in the South China Sea. Morphologically, S. annulatus n. sp. is distinct in having a tube with transverse rings and a forepart (i.e., anterior region) containing one arched row of elongated plaques on both sides of the dorsal furrow. Genome skimming, assembly, and annotation produced a nearly complete mitogenome of S. annulatus n. sp. with 15,553 bp nucleotides that encodes 13 protein-coding genes, two rRNA, and 22 tRNA. Phylogenetic analyses based on the mitochondrial cytochrome c oxidase I (cox1) gene and a concatenated dataset comprising the mitochondrial cox1 and 16S rRNA genes along with the nuclear 18S rRNA gene both strongly support the placement of S. annulatus n. sp. in the genus SclerolinumSouthward, 1961. Based on cox1, S. annulatus n. sp. is most closely related to an undescribed siboglinid from off Kushiro in Japan (“Pogonophora” sp. Kushiro-SK-2003). Transmission electron microscopy, microbial 16S rRNA amplicon sequencing, phylogenetic reconstruction, and stable isotope analyses together indicate that S. annulatus n. sp. hosts a single phylotype of sulfur-oxidizing endosymbionts.